Manuscript preservation strategy - Nabil HELILOU (Social Sciences Journal, 1970)
The manuscript represents a key element of the memory of individuals, peoples andnations, lies not important historical memory, but also because of its associationdimensions of patriotism, nationalism, and representation of the past of the nation andits present, it connects lectured the nation its past for the future will be based on thepresent and connected to the past of a prosperous, which contributes to the latter tocontinue generations and out of this importance, which is no different where two camethis article to illustrate a range of strategies that will keep the manuscript, especiallysince it faces a wave of challenges damage and loss ......Etc